2018
DOI: 10.1016/j.ijscr.2018.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic minimum saucerization and inferior-leaf meniscectomy for a horizontal tear of a complete discoid lateral meniscus: Report of two cases

Abstract: HighlightsArthroscopic minimum saucerization and inferior-leaf meniscectomy at 2-year follow-up.Preserving more than 10 mm width could obtain excellent clinical outcomes.Leaving more meniscal tissue might prevent meniscal extrusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Arthroscopic partial meniscectomy is an important technique for treating a horizontal tear of the lateral meniscus with excellent clinical outcomes [2,8,9]. This procedure is usually performed using the standardised anterolateral portal (ALP) and anteromedial portal (AMP), particularly in patients with mid-body and posterior horn tears of the lateral menisci.…”
Section: Introductionmentioning
confidence: 99%
“…Arthroscopic partial meniscectomy is an important technique for treating a horizontal tear of the lateral meniscus with excellent clinical outcomes [2,8,9]. This procedure is usually performed using the standardised anterolateral portal (ALP) and anteromedial portal (AMP), particularly in patients with mid-body and posterior horn tears of the lateral menisci.…”
Section: Introductionmentioning
confidence: 99%
“…repair vs meniscectomy/conservative treatment) and small sample sizes across included studies. Moreover, there have been 11 studies performed since the publication of this review [2, 3, 10, 26, 32, 43, 49, 52, 54, 59, 60]. With an increasing body of research published on the surgical treatment of HCTs over the past 5 years, an updated systematic review is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of knee osteoarthritis (OA) after discoid lateral meniscus (DLM) surgeries, previous long‐term studies regarding the outcomes of total and subtotal meniscectomies for DLM revealed high rates of osteoarthritic changes on postoperative radiographs [1, 18, 23, 26]. Although arthroscopic meniscal saucerization [10, 22, 24, 28, 29] with meniscal repair of peripheral detachments [2, 3, 5] is the gold‐standard treatment, it cannot completely prevent meniscal extrusion or chondromalacia of the lateral compartment [5].…”
Section: Introductionmentioning
confidence: 99%